Cambios en la práctica laboral de los profesionales de enfermería por la pandemia SARS-CoV-2/COVID-19 en una ciudad de Colombia (2021)
Objective: To determine the changes in the work practices of the nursing professional due to the SARS-CoV-2/COVID-19 pandemic. Materials and methods: Cross-sectional study in a population of nursing professionals who were working during the pandemic in the city of Cartagena, with a total sample of 115 individuals through snowball sampling, who were applied a survey virtually, a descriptive statistical analysis was performed. Results: The population consisted mostly of women with 82,6%, in ages between 30 and 40 years with 42,6% and 72,2% had undergraduate training. The 92,2% of nursing professionals state that with the SARS-CoV-2/COVID-19 pandemic there have been great changes in their work practice with the increase in more activities or tasks than were previously carried out, with the application of new strategies in the care and care of patients, with a high perception of risk in their workplace for contagion and economic difficulties at the work level due to the pandemic and they do not consider changing their work or occupational profile due to this situation that is happening. Conclusions: the current global health crisis exposes the need for professionals to adapt new labor practices and skills to the new demands of the labor market.